2018
DOI: 10.1091/mbc.e17-08-0495
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-6 KIF20B is required for efficient cytokinetic furrowing and timely abscission in human cells

Abstract: KIF20B is in the Kinesin-6 family that includes KIF23/MKLP1 and KIF20A/MKLP2. Previously we showed that mouse Kif20b regulates cerebral cortex growth and neural stem cell midbodies. Now we show KIF20B has a cell-autonomous role in regulating cytokinetic furrowing and abscission. KIF20B may coordinate late midbody maturation before abscission.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 57 publications
5
54
0
Order By: Relevance
“…As SAC does not affect shKIF20B‐induced mitotic and proliferation inhibition, and KIF20B plays a critical role in cytokinesis, consequently, we investigated at which mitotic phase shKIF20B suppressed HCC cells. First, we synchronized HepG2 cells at M‐phase by VX‐680 and measured the length of mitosis by checking the phosphorylation level of histone H3 (p‐H3), an M‐phase indicator .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As SAC does not affect shKIF20B‐induced mitotic and proliferation inhibition, and KIF20B plays a critical role in cytokinesis, consequently, we investigated at which mitotic phase shKIF20B suppressed HCC cells. First, we synchronized HepG2 cells at M‐phase by VX‐680 and measured the length of mitosis by checking the phosphorylation level of histone H3 (p‐H3), an M‐phase indicator .…”
Section: Resultsmentioning
confidence: 99%
“…11 KIF20B is a microtubule-associated protein specifically phosphorylated at M-phase and plays a critical role in cytokinesis. 12 In addition to its physiological roles in mitosis, KIF20B has also been found to play roles in solid tumors such as breast and bladder cancers. 13,14 Recently, we also reported the oncogenic role of KIF20B in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we showed that a loss-of-function mutation of the Kinesin-6 Kif20b in mice causes microcephaly (25,26). Kif20b protein localizes to the central spindle during furrowing, then to midbody flanks and finally to the constriction sites ( Figure 1G and (27,28). This dynamic localization during cytokinesis, suggests that Kif20b could play important roles in furrowing or abscission.…”
Section: Introductionmentioning
confidence: 75%
“…This dynamic localization during cytokinesis, suggests that Kif20b could play important roles in furrowing or abscission. We showed that in HeLa cells, Kif20b depletion caused subtle disruptions of furrowing speed, midbody maturation and abscission timing, but does not prevent abscission completion (27). This raised the question of whether Kif20b loss in NSCs would cause more severe defects in cytokinesis.…”
Section: Introductionmentioning
confidence: 98%
“…This method was previously described in (McNeely & Dwyer, 2020), based on first establishing SiR-tubulin for abscission duration studies in HeLa cells (Janisch et al, 2018). Briefly, E13.5 slabs were prepared as described above and placed apical surface down in a glass-bottom dish (MatTek, Ashland, MA, P35G-1.0–20-C) containing 50 nM SiR-Tubulin (Cytoskeleton, Denver, CO CY-SC002) in Final Culture Medium (described above).…”
Section: Methodsmentioning
confidence: 99%